2000
DOI: 10.1364/ao.39.003338
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and incoherent components of a synchrotron radiation spot produced by separate capillaries

Abstract: We discuss soft-x-ray focusing properties of separate capillaries. It is shown that a nonnegligible fraction of the synchrotron radiation beam transmitted by the capillary is modal. Experimental and theoretical data are discussed to explain the superposition pattern of x rays in the focal plane due to the interference phenomena of electromagnetic radiation propagating through separate capillaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Certain effects due to the capillary structure of the optics can still be seen in this regime [67,68]. Coherence effects could be seen from a small part of an area of array of capillaries, even if each acts as an incoherent source, if the propagation distance is large enough to satisfy (12).…”
Section: Wave Modeling and Nanocapillariesmentioning
confidence: 99%
“…Certain effects due to the capillary structure of the optics can still be seen in this regime [67,68]. Coherence effects could be seen from a small part of an area of array of capillaries, even if each acts as an incoherent source, if the propagation distance is large enough to satisfy (12).…”
Section: Wave Modeling and Nanocapillariesmentioning
confidence: 99%
“…One of the basic principles of x-ray beam propagation in a capillary channel is the possibility of a modal regime of radiation transmission, i.e., a capillary acts as an x-ray waveguide [8][9][10][11] but also allows the surface channeling of x-ray radiation. As a consequence, in addition to the established use of capillary optics to shape radiation in x-ray lithography, x-ray astronomy, crystal diffraction, x-ray fluorescence, neutron prompt gamma analysis, etc., the mode propagation of x rays in capillaries allows other unique applications, e.g., x-ray microscopy and focusing of coherent x-ray sources [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the structure of a focal spot was well described by the wave theory of passage of radiation through capillary structures 9 and resulted from an interference of waves. 18 Structural effects of the redistribution of radiation were also shown in experiments with single capillaries (monocapillaries) 11,19,20 and in experiments on multiple sliding reflection from a curved surface. 21,22 The observed effects confirmed the wave character of the dispersion of x-radiation in capillaries.…”
Section: Introductionmentioning
confidence: 92%